Study on Anatomical Structure and Properties of Durian (Durio spp.) and Rambutan - Nur Najwa Ibrahim (2018)
Wood anatomy information must be updated on an observation basis with new data analysis and discoveries. Wood anatomy is important to see the anatomical properties as it shows for analysis data such as fibre length, fibre diameter, and fibre wall thickness. The problem statement in this study is not too much information and not many researchers studied about this research from the previous. There are still lack information especially in research regarding anatomical properties of Durian (Durio spp.) and Rambutan (Nephelium spp.). The main objective of this study is to identify the potential of Durian (Durio spp.) and Rambutan (Nephelium spp.) as wood and wood products in construction and furniture industry related to anatomical characteristics and also to compare the anatomical properties, fibre dimension, and wood density at different position (bottom, middle, and top). Durian (Durio spp.) and Rambutan (Nephelium spp.) wood, which are between 10 years old was collected from Kampung Bukit Cina, Jerteh, Terengganu's area. To obtain anatomical data, cell proportions and fibre dimensions were performed to identify the nature of the wood anatomy and Durian (Durio spp.) and Rambutan (Nephelium spp.). For result obtained, at the diameter of the fibres alone showed a significant level in the outcome of this study between the two species, which is (P=0.018). From the result Analysis of Variance (ANOVA) for density of wood, which is Durian (Durio spp.) and Rambutan (Nephelium spp.), on species had been the significant value (P=0.006). From the identification wood density between durian (Durio spp.) and Rambutan (Nephelium spp.), Rambutan (Nephelium spp.) wood has the higher density than Durian (Durio spp.). Between each portion, which is bottom, middle, and top, middle portion has the higher density. Accordingly, it has a good impact on the construction and furniture industry. The results show that it can identify the nature of wood and the density of wood. It can also be a comparison between wood species.